Rural Transport : Improving its Contribution to Growth and Poverty Reduction in Sub-Saharan Africa - Banjo, George; Gordon, Henry; Riverson, John (World Bank, Washington, DC, 2014)
Poverty reduction is a long-standing development objective of many developing countries and their aid donors, including the World Bank. To achieve this goal, these countries and organizations have sought to improve smallholder agricultural productivity in Sub-Saharan Africa (SSA) as part of a broader rural development agenda aimed at providing a minimal basket of goods and services in rural areas to satisfy basic human needs. These goods and services include not only food, health care, and education, but also infrastructure. As a result, rural transport remains a constraint to increasing agricultural productivity, achieving rural growth, and thus alleviating rural poverty. The first major finding of the review of rural transport theory and practice is that many of the approaches needed to improve the impact of rural transport interventions on poverty reduction are known, particularly from the work of the Rural Travel and Transport Program (RTTP) of Sub-Saharan Africa Transport Policy Program (SSATP). Unfortunately, many of the recommended approaches remain untested within Sub-Saharan Africa beyond the pilot scale, notwithstanding their influence on rural transport policy and project design in other operational regions of the Bank. For SSA, these are missed opportunities. Even where SSA countries have applied these approaches, institutional and financial sustainability and scaling up local successes remain significant challenges for both their agriculture and transport sectors. The second key finding is that rural households are rarely the point of focus in the design of rural transport interventions in SSA, even though a methodology to allow this focus has been developed and successfully tested in several pilot projects since the 1980s, the result is that the transport needs of rural households continue to be analyzed and understood by means of an indirect assessment of those needs, which means that most projects have a less than desirable impact on improving the rural access and mobility situation of such households.